The Development of Web-Based Teaching Materials Integrated with Indonesian Folklore for Indonesian Language for Foreign Speakers Students - Yulianeta, Yulianeta; Yaacob, Aizan; Lubis, Arif Husein (Universitas Negeri Makassar, 2022)
Although the preservation of the Indonesian culture is deemed beneficial, the lack of folklore texts readily available for instructional purposes makes teaching and learning the Indonesian culture challenging. This study aims to develop web-based teaching materials, integrated with Indonesian folklore for intermediate- level students of Indonesian for foreign speakers (BIPA). A Research and Development (R&D) method was employed with a 4D research model (Define, Design, Develop, and Disseminate). Four teachers and seven students were purposively selected, based on prior experience in teaching BIPA and ownership of a device and ability to operate a software. A questionnaire, expert validation sheet, users assessment sheet, and interview guide were employed to obtain the expected data. The results of the study revealed that all teachers had used textbooks and the Internet, but not all teachers used enrichment materials from the government. They further stated that they were interested in the development of teaching materials with folklore texts. The expert validation results showed that the developed web-based teaching materials was feasible with a very good predicate. Based on a limited trial (independently) by users, BIPA teachers and students responded that the prototype was feasible with a very good predicate